1997
DOI: 10.1210/endo.138.11.5652
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Estrogen Receptors α and β mRNA During Differentiation of Human Osteoblast SV-HFO Cells

Abstract: Estrogens have been shown to be essential for maintaining a sufficiently high bone mineral density and ER alpha expression has been demonstrated in bone cells. Recently, a novel estrogen receptor, estrogen receptor beta (ERbeta) has been identified. Here we demonstrate that also ERbeta is expressed in human osteoblasts, and that ER alpha and ERbeta are differentially expressed during human osteoblast differentiation. ERbeta mRNA expression increased gradually during osteoblast culture, resulting in an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(43 citation statements)
references
References 0 publications
4
36
0
1
Order By: Relevance
“…In the male genital tract, Hess et al (1997) detected mRNA encoding ERβ in the efferent ductules, all regions of the epididymis, the vas deferens and prostate of adult male rats. Consistent with the documented effects of oestrogens on bone physiology (Turner et al, 1994), expression of mRNAs encoding ERα and ERβ have been detected in rat osteoblasts isolated from 1-day-old rat bone (Onoe et al, 1997) and a human osteoblast cell line (Arts et al, 1997). In both rat and human osteoblasts, expression of mRNA encoding ERβ detected by semi-quantitative PCR appeared to be differentially regulated compared with mRNA encoding ERα (Arts et al, 1997;Onoe et al, 1997).…”
Section: Pattern Of Expression Of Mrna Encoding Erβsupporting
confidence: 56%
“…In the male genital tract, Hess et al (1997) detected mRNA encoding ERβ in the efferent ductules, all regions of the epididymis, the vas deferens and prostate of adult male rats. Consistent with the documented effects of oestrogens on bone physiology (Turner et al, 1994), expression of mRNAs encoding ERα and ERβ have been detected in rat osteoblasts isolated from 1-day-old rat bone (Onoe et al, 1997) and a human osteoblast cell line (Arts et al, 1997). In both rat and human osteoblasts, expression of mRNA encoding ERβ detected by semi-quantitative PCR appeared to be differentially regulated compared with mRNA encoding ERα (Arts et al, 1997;Onoe et al, 1997).…”
Section: Pattern Of Expression Of Mrna Encoding Erβsupporting
confidence: 56%
“…Studies by our own and other groups have indeed shown that ERβ is expressed in osteoblasts of growing bone in the rat. ERβ is also detected in osteoblastic cell lines, pointing to a possible role of ERβ in bone formation (Onoe et al 1997, Arts et al 1998. The relevance of these observations in the human is, however, unclear, since the only known human patient lacking functional ERα displays severe osteoporosis (Smith et al 1994).…”
Section: Human Erβmentioning
confidence: 99%
“…The primer at aa-3 has an overlapping region (about 15-20 bp) that begins at the next amino acid in the deletion construct (i.e. aa 51 in ⌬3-50 hER ␣/␤ ) In a separate, simultaneous reaction, another set of primers that span from the last amino acid deleted (this primer also contains an overlap region of about [15][16][17][18][19][20] bp that begins at aa 3 and spans to upstream sequences in the vector) to the EcoRV site in pcDNA3.1hER ␣/␤ are PCR-amplified. The PCR products from both reactions were purified using Wizard PCR Prep DNA purification system (Promega, Madison, WI).…”
mentioning
confidence: 99%